Quantify retinal structure in high-altitude residents with and without high altitude polycythemia - Jinlan Ma; Haoyu Niu; Changjing Han; Yi Qu (BMC Ophthalmology, 2023)
Abstract Background To assess retinal structural parameters in high-altitude (HA) residents with and without high altitude polycythemia (HAPC) and to elucidate the relationship between retinal structural parameters and hemoglobin (HGB). Methods This cross-sectional study included 55 HAPC patients and 52 healthy HA residents. Retinal structural parameters included retinal nerve fiber layer (RNFL) thickness, optic nerve head (ONH) parameters and retinal vessel diameter. RNFL thickness were acquired from spectral domain optical coherence tomography (SD-OCT) built-in software. ONH parameters including neuroretina rim height, cup area, disc area and vertical cup/disc ratio were obtained by OCT built-in software and ImageJ software. Retinal vessel measurements including central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE) and AVR (artery/vein ratio) were calculated by revised formulas for summarizing retinal vessel diameters. All parameters were compared between HAPC group versus healthy HA group. The associations between retinal parameters and HGB were assessed by Pearson correlation analyses. Results In comparison of HAPC group versus healthy HA group, RNFL thickness was thicker in the nasal quadrant of the optic disc in HAPC group (74.82 ± 14.4 VS. 66.06 ± 13.71 μm, P = 0.002). Bigger disc area and bigger cup area were also observed in HAPC group (all P < 0.05). Meanwhile, the value of CRVE was higher in HAPC group which suggested that retinal veins dilated significantly in HAPC patients (P < 0.001), however, CRAE and AVR were comparable between groups. Pearson analyses revealed that HGB was positive correlated with CRVE in HAPC group (r = 0.469, P = 0.003). Conclusions long-term HA exposure secondary HAPC could result in thickened RNFL, enlarged ONH and dilated retinal veins. Moreover, increased blood viscosity caused by HGB should be responsible for dilated veins, but not for thickened RNFL and enlarged ONH. This study deepens the understanding of the impact of HA environment on retina.